Applications of Contrastive Analysis in Translation - Al- Amin, Awatif (Gezira Journal of Educational Sciences and Humanities, 2018)
The study aimed at exploring the importance of contrastive analysis in translation. The analytical comparative method was adopted where structures of Arabic and English are presented, illustrated with examples and compared. The most important results revealed: contrastive linguistic analysis helps to determine the translation difficulties. Pointing out the similarities and differences between the SL and TL facilitate translation. Teachers of translation are recommended to perform contrastive and error analysis  in their classes.